2010
DOI: 10.1021/ic100882u
|View full text |Cite
|
Sign up to set email alerts
|

Highly Emissive Cyclometalated Rhenium Metallacycles: Structure−Luminescence Relationship

Abstract: We report on a series of new self-assembled cyclometalated dirhenium(I) metallacyclic complexes via an unprecedented rhenium-mediated C-H bond activation and the relationship between their structures and luminescence properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…The product is air‐ and moisture‐stable and is soluble in polar organic solvents. A recent review on Re I metallacycles15 has revealed that all dinuclear Re I complexes are bridged through O , O ‐,11b N , N ‐8 or N , C ‐donor atoms 8. In fact, multinuclear Re I assemblies with asymmetric coordination environments are rare 15,16…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The product is air‐ and moisture‐stable and is soluble in polar organic solvents. A recent review on Re I metallacycles15 has revealed that all dinuclear Re I complexes are bridged through O , O ‐,11b N , N ‐8 or N , C ‐donor atoms 8. In fact, multinuclear Re I assemblies with asymmetric coordination environments are rare 15,16…”
Section: Resultsmentioning
confidence: 99%
“…Because of the large spin–orbit coupling (SOC) and hence efficient intersystem crossing (ISC) shown by the Re I metal centre, structureless and broad phosphorescent emission from the lowest‐energy triplet excited state is most often observed 7. Such a deactivation route from the triplet metal‐to‐ligand charge‐transfer ( 3 MLCT) state is also attributed to 1) a radiative lifetime in the nanosecond range, 2) a prominent rigidochromism and 3) emission quenching by dioxygen 7,8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,[27][28][29][30][31] For the construction of such dirhenium metallacycles, bis(chelating) organic clips are usually utilized in combination with flexible dipyridyl linkers. [27,30] Owing to their efficacy in different fields such as luminescent sensors, imaging, and photocatalytic CO 2 reduction, Re I -based complexes continue to attract considerable interest for various modern applications. [32][33][34][35] Although the supramolecular chemistry of rhenium has evolved tremendously, the true potential of its congener manganese remains unrealized.…”
Section: Introductionmentioning
confidence: 99%
“…Lu and co-workers [180] initiated the synthesis of a family of cyclometalated rhenium metallacycles, in which cyclometalating ligands have a beneficial effect on luminescence yields. A facile onepot synthesis of the dinuclear rhenium(I)-cyclometalated com-…”
mentioning
confidence: 99%